Agronomic biofortification of rice with selenium - Alifar, Nafiseh (2015)
Selenium (Se) is one of the most important micronutrient for humans and animals. There is a narrow range between its deficiency and toxicity. Se by itself does not commonly cause illness but it contribute to different disease such as heart disease, hypothyroidism, and a weakened immune system. Se concentration in Malaysian soils is very low. In most cases Se deficiency can be corrected by the application of Se as fertilizer into the soils, which is termed as agronomic biofortification. The main source of Se for most people in Asian countries is rice, but its concentration may be insufficient to maintain human health. Agronomic biofortification can be done to improve Se content in rice production. This study was undertaken to determine Se adsorption and desorption of Malaysian rice soils, to evaluate the Se efficiency of selected rice genotypes and to determine the response of Se application on rice. A field trial was carried out with five different selenium rates at 0, 5, 10, 20, 40 mg Se/kg fertilizer on MR219 rice variety, a popular variety used in Malaysia. The Se rates chosen did not affect the rice yield, the grain selenium concentration and the soil selenium concentration which means that for fortifying rice grain we should increase the level of Se. To obtain a better understanding of the extent to which added selenite would be retained by the soil, an investigation of selenite adsorption and desorption by rice growing soils was carried out. Sorption and desorption isotherms of different soils collected from Tg. Karang, Teluk Intan I, Teluk Intan II, Bagan Serai, Guar Cempedak h, Kangar, Jertih, Kota Bharu, Machang and UPM in Malaysia were determined by using a batch method. The Freudlich and Langmuir equation was well fitted to the obtained sorption and desorption isotherms. Adsorption data in this study revealed an L shape isotherm that could be explained by the high affinity of the soils for the Se sorption at low concentration which then decreased as the concentration increased. It is also concluded that selenium availability to plants is affected by soil pH, organic matter content and clay minerals. Sorption of selenite increases with decreasing pH and increasing organic matter. The result showed that the selenium desorption hysteresis in different soils was due to irreversible Se inner sphere binding to the edge of the minerals. In the next experiment, six rice varieties collected from Penang (MR211, MR219, MR220, MR232, MR253, MR263) were studied at three levels (0, 20 and 200 μg Se/L) to investigate Se accumulation in roots and shoots. These six varieties showed significant effects on Se uptake in shoots and roots but different Se concentrations had no significant effects on root parameters. The results showed that Se accumulation in shoots in all the varieties is greater than Se accumulation in roots. With MR253 having the lowest amount. A greenhouse trial was conducted with 3 varieties from the solution culture study, soil chosen from the adsorption studies and Se rates of 0, 100, 300, 500 and 700 g ha-1. The aim was to assess the Se concentration and the Se uptake in different part of the plants, especially in rice grain, but also to evaluate the effect of selenium on yield and some yield components. In this study, it was observed that except for rice yield, 1000 grain yield and total shoot dry weight other parameters such as leaf, culm and rice grains yield of rice varieties as well as total Se uptake and grain Se uptake were affected by different selenium rates. Among the different Se levels used, the level of 500 g ha-1 of Se would be the recommended rate in order to increase the Se concentration in grain. Between the Se concentration in grain and leaf, a positive correlation was observed. Also, there was a correlation between Se uptake and Se accumulation in the rice plant.